Part orientation optimisation for the additive layer manufacture of metal components. Issue 5 (September 2016) - Morgan, H.; Cherry, J.; Jonnalagadda, S.; Ewing, D.; Sienz, J.
Abstract In a number of additive layer manufacturing processes, particularly for metals, additional support structure is required during the build process to act as scaffolding for overhanging features and to dissipate process heat. Such structures use valuable raw materials and their removal adds to post processing time. The objective of this study was to investigate whether a simple, single objective optimisation technique could be used to find the best orientation of the part, that would minimise the volume of support needed during the build. Not only reducing waste but potentially providing an effective and consistent approach for inexperienced users to orient components during manufacture. Software was developed using MatLab with an unconstrained optimisation algorithm implemented to search the different rotations of the part and identify the configuration with the least requirement for support volume. The algorithm was gradient based, and so multiple starting points were used to identify a global minimum. The efficacy of the algorithm is illustrated with three different case studies of increasing complexity. Additionally, the component of the final study was manufactured, which allowed a comparison between the algorithm's results and the orientations chosen by experienced operatives. In two of the three case studies, the software was able to find good solutions for the support volume minimisation. For the manufactured part, only one of the results matched the orientation chosen by the operators, the other was orientated in a similar way but the difference added significantly to the required support volume. Future developments of the software would benefit from incorporating the expertise of the manufacturing operative.